2018
DOI: 10.1111/1365-2664.13150
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, temporal and experimental: Three study design cornerstones for establishing defensible numeric criteria in freshwater ecosystems

Abstract: Nutrient over‐enrichment increasingly threatens global water resources. Stressor‐response studies specifically designed to identify levels of nutrients strongly associated with undesirable ecological conditions are needed to inform numeric nutrient criteria that protect inland waters. Diatoms are important components of aquatic life, which support higher trophic levels and are sensitive to nutrient enrichment. We tested a framework that relies on stressor‐response modelling of phosphorus (P) enrichment and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…However, developing nutrient stressor–response relationships and translating them into meaningful, scientifically defensible benchmarks for managing P and N within MAP streams will require increasing sampling frequency and spatial coverage to more accurately represent the entire region, as well as refinements to sampling methodology. Future studies that include greater spatial coverage within the region, temporal sampling, and experiments to control for confounding factors will further the development of diatom‐based measures for evaluating ecological responses to BMPs within the MAP (Bowes et al, 2007; Taylor et al, 2018). Current study results were only significant for TP, but including BMPs that reduce N export from agricultural watersheds in the Mississippi River basin can also help reduce widespread coastal hypoxia in the Gulf of Mexico (Turner and Rabalais, 2003; Alexander et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, developing nutrient stressor–response relationships and translating them into meaningful, scientifically defensible benchmarks for managing P and N within MAP streams will require increasing sampling frequency and spatial coverage to more accurately represent the entire region, as well as refinements to sampling methodology. Future studies that include greater spatial coverage within the region, temporal sampling, and experiments to control for confounding factors will further the development of diatom‐based measures for evaluating ecological responses to BMPs within the MAP (Bowes et al, 2007; Taylor et al, 2018). Current study results were only significant for TP, but including BMPs that reduce N export from agricultural watersheds in the Mississippi River basin can also help reduce widespread coastal hypoxia in the Gulf of Mexico (Turner and Rabalais, 2003; Alexander et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Diatom assemblages can be excellent indicators of nutrient status, and researchers have developed many indices to assess trophic status of water bodies on multiple continents (Kelly and Whitton, 1995;Bellinger et al, 2006;Stevenson et al, 2008;Tan et al, 2013). Additionally, previous observational and experimental work has shown that diatom assemblage responses to nutrient enrichment gradients are robust, despite temporal shifts in species composition associated with variation in potentially confounding factors (Taylor et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As one example, Taylor et al (2018) recently demonstrated the usefulness of employing coupled field studies with experimental stream mesocosm experiments to identify ecological thresholds associated with P enrichment. As one example, Taylor et al (2018) recently demonstrated the usefulness of employing coupled field studies with experimental stream mesocosm experiments to identify ecological thresholds associated with P enrichment.…”
Section: Multiple Stressors and Mixturesmentioning
confidence: 99%
“…Ideal studies for investigating nutrient effects would pair experimental and field-based approaches and include measurement of nutrient forms relevant to the question at hand and to management (e.g., Taylor et al 2018). To achieve this goal, we first recommend more complete and transparent data reporting (Reichman et al 2011;Lortie 2014), as several studies measured total nutrient fractions but either did not report these measures or measured them only prior to the experimental addition of nutrients.…”
Section: Recommendationsmentioning
confidence: 99%